2023
DOI: 10.1371/journal.pone.0286745
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle mass index and all-cause mortality risk in adults: A systematic review and meta-analysis of prospective cohort studies

Abstract: Objective The relationship between low skeletal muscle mass index (SMI) and all-cause mortality risk in the general adults remains unclear. Our study was conducted to examine and quantify the associations between low SMI and all-cause mortality risks. Methods PubMed, Web of Science, and Cochrane Library for primary data sources and references to relevant publications retrieved until 1 April 2023. A random-effect model, subgroup analyses, meta-regression, sensitivity analysis, and publication bias were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Similarly, a recent systematic review and meta-analysis of 16 studies conducted across the world (including countries in Asia, North America, South America, Europe, and Australia) concluded that low skeletal mass index (SMI; skeletal muscle mass per unit of height) was associated with increased all-cause mortality, even when stratified by age categories (i.e., in people aged less than 45 years, aged 45–65 years, and in those over the age of 65 years). The pooled relative risk of all-cause mortality was 1.57 (95% CI: 1.25–1.96) in those with the lowest SMI and the risk of all-cause mortality associated with low SMI was greatest in those with a higher BMI [ 35 ]. Subgroup analysis of those over the age of 65 years demonstrated that a low SMI could increase all-cause mortality risk by 56%, clearly illustrating the importance of SKM mass for longevity.…”
Section: Muscle Mass and Ageingmentioning
confidence: 99%
“…Similarly, a recent systematic review and meta-analysis of 16 studies conducted across the world (including countries in Asia, North America, South America, Europe, and Australia) concluded that low skeletal mass index (SMI; skeletal muscle mass per unit of height) was associated with increased all-cause mortality, even when stratified by age categories (i.e., in people aged less than 45 years, aged 45–65 years, and in those over the age of 65 years). The pooled relative risk of all-cause mortality was 1.57 (95% CI: 1.25–1.96) in those with the lowest SMI and the risk of all-cause mortality associated with low SMI was greatest in those with a higher BMI [ 35 ]. Subgroup analysis of those over the age of 65 years demonstrated that a low SMI could increase all-cause mortality risk by 56%, clearly illustrating the importance of SKM mass for longevity.…”
Section: Muscle Mass and Ageingmentioning
confidence: 99%
“…Skeletal muscle plays a key role in metabolic function, facilitates glucose uptake and storage, and is related to physical performance [21]. Skeletal muscle is the human body's biggest organ, 20-40% of total body weight in women and 30-50% in men, and serves as the body's principal protein storage organ [22]. Therefore, it is necessary to have an exercise program to support the manipulative skills of Down syndrome children.…”
mentioning
confidence: 99%